Lomba Ranking 1 Dan Donasi Buku: Upaya Meningkatkan Pengetahuan Siswa Di Pulau Jaloh - Husna, Asmaul; Ramses; Himmi, Nailul; Hasanah, Raja Syiratin (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Jaloh Island is one of the islands in the Riau Islands Province which is the location of SDN 10 Bulang and SMPN 19 Batam. Students on this island have difficulty accessing in and out of the island, thus hampering various distributions, including accessing reading resources. For this reason, 1st place competitions and book donations were carried out for existing schools. This activity is to see knowledge and increase students' reading interest. The activity lasted for two days, with previous mapping and division of the implementation team. The results of this activity gave students enthusiasm in taking part in competitions and reading the donated books, where 50 books were donated